Sprachenpolitik in Europa – Tatsachen und Perspektiven - Ehlich, Konrad (Stellenbosch Papers in Linguistics Plus, 2012)
This paper characterizes the linguistic situation in Europe in the context of the global languagesituation. It describes the significance of the "Project Nation" for the European national languages.European unification after World War II is examined in terms of its linguistic consequences in anumber of linguistically sensitive areas such as the economy and science. The language-politicalactivities of the European Council and the European Union are characterized. A distinct languageconcept is necessary for furthering the linguistic development of Europe – such a language conceptshould take into account the teleological, the gnoseological and the communitary dimension oflanguage in equal measure. I argue against a pseudo-solution for the language question through thepropagation of a "lingua franca" and instead plead for a complex linguistic education concept forEurope, in which multilingualism is regarded and language-politically stated as a cultural andintercultural challenge. Central to this concept is the development of a workable hermeneutics.Keywords: Schlüsselbegriffe: Europa, „Projekt Nation“, europäische Vereinigung, Europarat, EuropäischeUnion, „lingua franca“, Mehrsprachigkeit, Interkulturalität, Hermeneutik, teleologische,gnoseologische, kommunitäre Dimension von SpracheEurope, “Project Nation”, European unification, European Council, European Union,“lingua franca”, multilingualism, interculturalism, hermeneutics, teleological, gnoseological,communicatory dimension of language